2017
DOI: 10.1186/s40880-016-0169-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of apoptosis-stimulating P53-binding protein 1 and 2 and their relationships with clinical characteristics of esophageal squamous cell carcinoma patients: a retrospective study

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is a leading cause of cancer-related death, and new prognostic biomarkers are urgently needed. Apoptosis-stimulating P53-binding protein 1 (ASPP1) and 2 (ASPP2) have been reported to play important roles in the development, progression, metastasis, and prognosis of cancers, but their roles in ESCC have not been elucidated. In this study, we examined the expression of ASPP1 and ASPP2 in ESCC to evaluate their prognostic values.MethodsThe protein expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…examined the protein expression of ASPP1, ASPP2, and P53 in 175 specimens of ESCC by immunohistochemical staining. Their results showed that the protein expression level of ASPP2 was significantly higher in cancerous tissues than in paired noncancerous tissues [9]. In our study, the frequency of ASPP2 protein expression was greatest in NEE and decreased gradually during the evolution of esophageal carcinogenesis, with only 49.3% of ESCC showing high expression of ASPP2 protein by IHC.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…examined the protein expression of ASPP1, ASPP2, and P53 in 175 specimens of ESCC by immunohistochemical staining. Their results showed that the protein expression level of ASPP2 was significantly higher in cancerous tissues than in paired noncancerous tissues [9]. In our study, the frequency of ASPP2 protein expression was greatest in NEE and decreased gradually during the evolution of esophageal carcinogenesis, with only 49.3% of ESCC showing high expression of ASPP2 protein by IHC.…”
Section: Discussionsupporting
confidence: 45%
“…ASPP2 belongs to the evolutionarily conserved ASPP family of proteins, alongside ASPP1 and iASPP. It is commonly considered a tumor suppressor, and its expression is often reduced in malignant tumors [7–9]. Recent studies have also shown that ASPP2 is a key mediator of RAS‐induced senescence, a property independent of p53 [10–12], suggesting that ASPP2 can suppress tumor growth through p53‐dependent and ‐independent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…First, we investigated mutations in genes that play a key role in the adenoma-carcinoma model of CRC such as APC, KRAS, TP53, and binding/transactivated genes. We found the rs373141354 variant in the PPP1R13B gene (p.Gly866Arg), which assists TP53 activation during the cell apoptosis and lowers their ability shared by all subjects HRLS group [33]. Although TP53 is known to be rarely mutated in LS [34], our findings can be attributed to the high efficiency of TP53 in maintaining genomic integrity by arresting cells with mutated or damaged DNA in the G1 phase of the cell cycle to enable the repair mechanism or induce the apoptosis pathway [35].…”
Section: Discussionmentioning
confidence: 82%
“…In this study, 11 members' (3 HRLS, 4 IRLS, and 6 LRLS) germline genomes were fully sequenced and their medical, environmental, and behavioral data were carefully analyzed. Individual and familial characterizations are described in Table 33.34% (1/3) HRLS, 0% (0/4) IRLS, and 50% (3/6) LRLS. Concerning lifestyle, 66.66% of HRLS recorded high brine and meat consumption, 100% of IRLS had a high fat consumption, and 75% of LRLS presented high meat and fat consumption.…”
Section: Clinical Characterization Of the Pedigree Membersmentioning
confidence: 99%
“…TP53 is a tumorsuppressor gene but is mutated in about 50% of cancers, thereby regulating the proliferation of various tumor cells (Egashira et al, 2011). A high expression of TP53 has been observed in many malignancies (Hinds et al, 1990;Iggo et al, 1990;Samuels-Lev et al, 2001), including esophageal cancer (Huang et al, 2014;Yao et al, 2014;Xie et al, 2017). Several studies found that the expression of TP53 in cancer tissues of ESCC patients could be utilized to analyze the survival and prognosis of esophageal cancer (Yao et al, 2014;Xie et al, 2017;Melling et al, 2019).…”
Section: Discussionmentioning
confidence: 99%